Pengaruh Pemberian Ekstrak Peperomia pellucida Terhadap Penurunan Ekspresi Tumor Necrosis Factor Alpha (TNF-α) Pada Ginjal Tikus Wistar Jantan Yang Mendapat Pajanan Asap rokok - Nerawati, Maria Fransiska; Farida Anggraini Soetedjo; Heru Setiawan (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2024)
Introduction: Exposure to cigarette smoke causes oxidative stress and inflammatory responses through free radicals. Tumor Necrosis Factor Alpha is a pro-inflammatory cytokine that exacerbates kidney inflammation. The administration of exogenous antioxidants and anti-inflammatory agents is expected to prevent kidney injury caused by cigarette smoke exposure. Peperomia pellucida, also known as